Влияние структуры магнитного поля Земли на теоретический расчёт скорости движения плазмы, индуцированного ветром нейтральной среды - Гринченко, Сергей Владимирович; Дзюбанов, Дмитрий Анатольевич (НТУ "ХПИ", 2016)
Представлено глобальное распределение углов наклонения и склонения магнитного поля Земли в северном полушарии. Выводятся формулы для вычисления скорости движения плазмы, индуцированного ветровым движением нейтральной среды, для случаев учёта или неучёта величины угла склонения магнитного поля Земли.

Global distribution of Earth’s magnetic field inclination and declination in the northern hemisphere is presented. Formulas for calculating the plasma velocity, induced by wind motion of neutral environment, in cases of taking into account, or no taking into consideration the declination of the Earth’s magnetic field are deduced.
Influence of Earth’s magnetic field structure on a theoretical calculation of the plasma velocity induced by neutral environment wind
Keywords: угол склонения; угол наклонения; модель IGRF; ионосферная плазма; вектор напряжённости; earth’s magnetic field; IGRF model; ionospheric plasma velocity